Akulturasi Budaya Lokal dalam Pelaksanaan Hak dan Kewajiban Suami Istri (Kajian terhadap Corak Ahwal Syakhshiyyah di Masyarakat Muslim Lokal Desa) - Dahlan, Ahmad; Hazizah, Nur; Dewi , Wina Kurnia; Antisah, Fina (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Universitas Qomaruddin, Gresik, Indonesia, 2025)
The implementation of the rights and obligations of husbands and wives in rural Muslim communities does not take place within a normatively sterile framework; rather, it is shaped by a dynamic interaction between Islamic teachings and deeply rooted local cultures. In practice, the norms of Ahwal Syakhshiyyah are not always applied textually as prescribed in classical fiqh literature, but instead undergo processes of interpretation and adjustment in accordance with the social realities of village communities. This study aims to analyze how local cultural acculturation shapes the implementation of spousal rights and obligations, as well as the patterns of Ahwal Syakhshiyyah application in the context of rural Muslim societies. This study employs a qualitative approach using a library research method, analyzing normative sources of Islamic law, statutory regulations, and relevant sociological and anthropological literature. The data are examined through content analysis and contextual interpretation to identify patterns of integration between Islamic legal norms and local cultural values. The findings indicate that local culture plays a significant role in shaping role distribution, decision-making processes, and the resolution of household conflicts. On the one hand, patriarchal patterns that position the husband as the primary authority figure remain evident; on the other hand, more balanced husband–wife relations have emerged, particularly in economic matters and family deliberation. These findings underscore that Ahwal Syakhshiyyah in rural Muslim communities functions as a living law that is adaptive and contextual. This study contributes to the development of Islamic family law by emphasizing the importance of a contextual approach to ensure that the values of justice, compassion, and household harmony can be realized without compromising the substantive principles of Islamic teachings.